New approaches to the effects of Si on sugarcane ratoon under irrigation in Quartzipsamments, Eutrophic Red Oxisol, and Dystrophic Red Oxisol - Costa, Milton G. [UNESP]; de M. Prado, Renato [UNESP]; Sarah, Marcilene M. Santos [UNESP]; Palaretti, Luiz F. [UNESP]; de C. Piccolo, Marisa; Souza Júnior, Jonas P. [UNESP] (Springer Nature, 2023)
Background: C:N:P homeostasis in plants guarantees optimal levels of these nutrients in plant metabolism. H However, one of the causes to the effects of deficit irrigation is the loss of C:N:P homeostasis in leaves and stems that causes reduction in the growth of sugarcane. Being able to measure the impact of water deficit on C:N:P homeostasis in plants from the stoichiometric ratios of the concentrations of these nutrients in leaves and stems. This loss causes a decrease in nutritional efficiency, but can be mitigated with the use of silicon. Silicon favors the homeostasis of these nutrients and crop productivity. The magnitude of this benefit depends on the absorption of Si by the plant and Si availability in the soil, which varies with the type of soil used. Thus, this study aims to evaluate whether the application of Si via fertigation is efficient in increasing the absorption of Si and whether it is capable of modifying the homeostatic balance of C:N:P of the plant, causing an increase in nutritional efficiency and consequently in the production of biomass in leaves and stems of sugarcane ratoon cultivated with deficient and adequate irrigations in different tropical soils. Results: Water deficit caused biological losses in concentrations and accumulation of C, N, and P, and reduced the nutrient use efficiency and biomass production of sugarcane plants cultivated in three tropical soils due to disturbances in the stoichiometric homeostasis of C:N:P. The application of Si increased the concentration and accumulation of Si, C, N, and P and their use efficiency and reduced the biological damage caused by water deficit due to the modification of homeostatic balance of C:N:P by ensuring sustainability of the production of sugarcane biomass in tropical soils. However, the intensity of attenuation of such deleterious effects stood out in plants cultivated in Eutrophic Red Oxisols. Si contributed biologically by improving the performance of sugarcane ratoon with an adequate irrigation due to the optimization of stoichiometric ratios of C:N:P; increased the accumulation and the use efficiency of C, N, and P, and promoted production gains in biomass of sugarcane in three tropical soils. Conclusion: Our study shows that fertigation with Si can mitigate the deleterious effects of deficient irrigation or potentiate the beneficial effects using an adequate irrigation system due to the induction of a new stoichiometric homeostasis of C:N:P, which in turn improves the nutritional efficiency of sugarcane cultivated in tropical soils.
Keywords: Beneficial element; Fertigation with Si; Homeostatic balance of C:N:P; Saccharum officinarum L; Tropical soils